Ductal abnormalities as primary findings on breast ultrasonography: a literature review and proposed classification - Ken Oba; Hiroko Tsunoda; Woo Kyung Moon (Ultrasonography, 2025)
Ductal abnormalities, such as dilated ducts with intraductal lesions, are frequently the primary ultrasound findings prompting biopsy and resulting in the early diagnosis of breast cancer or high-risk lesions. However, the Breast Imaging Reporting and Data System (BI-RADS) ultrasound lexicon provides limited guidance on these findings, categorizing them merely as associated features. To address this limitation, this review presents a critical analysis of existing literature and proposes a new classification encompassing three distinct subtypes: dilated ducts alone, dilated ducts with intraductal echoes, and intraductal masses. Additionally, an interpretation algorithm is introduced that incorporates lesion size and suspicious ultrasound features to guide BI-RADS assessment. This structured approach aims to standardize terminology, improve diagnostic accuracy, and promote consistent management of ductal abnormalities, especially in asymptomatic women.